Production of nanoscale copper compounds and evaluation of their qualitative and dimensional composition - Zadoshenko E.G.; Ozerov S.V. (Научно-технический вестник Брянского государственного университета)
In this work, nanoscale copper compounds were obtained by thermal decomposition of copper capronate. Selected modes of pyrolysis of organic salt. Particle diameter calculations based on X-ray fluorescence analysis and sedimentation analysis are presented. It has been established that during the decomposition of copper capronate, copper (I) oxide particles and Cu particles, whose size is 30 nm and 11 nm, are formed.